Nano titanium oxide / carbon composite surface modified titanium-based bipolar plate, preparation method and application

By using the method based on methane pyrolysis carbon deposit effect and oxygen vacancies, the problems of uneven coating and poor binding force in the surface modification technology of titanium bipolar plates are solved, and the high conductivity and corrosion resistance of titanium-based bipolar plates are achieved, which is suitable for large-scale production.

CN119695185APending Publication Date: 2025-03-25ZHENGZHOU UNIVERSITY OF LIGHT INDUSTRY
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411859339.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-17
Publication Date
2025-03-25

AI Technical Summary

Technical Problem

The existing titanium bipolar plate surface modification technology has problems such as uneven coating, poor bonding force, high process cost and complex operation, which is difficult to meet the high-performance demand of fuel cells for bipolar plates.

Method used

The surface modification method of titanium-based bipolar plate based on methane pyrolysis carbon deposit effect and oxygen vacancies was used to remove the oxide film by chemical corrosion to form a nickel catalytic layer, and nano-amorphous carbon and oxygen vacancies were used to form nano-amorphous carbon and oxygen vacancies titanium oxide to prepare a nano-titanium oxide/carbon composite layer.

Benefits of technology

It realizes the high conductivity, corrosion resistance and high quality of the modified layer of the titanium-based bipolar plate. It has simple process and low cost, and is suitable for large-scale production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119695185A_ABST
    Figure CN119695185A_ABST
Patent Text Reader

Abstract

The invention discloses a nano titanium oxide / carbon composite surface modified titanium-based bipolar plate as well as a preparation method and application thereof. The method comprises the following steps: removing oil stains on the surface of the titanium bipolar plate by using alcohol; an oxidation film on the surface of the titanium bipolar plate is removed in an ammonium bifluoride solution to form a nano titanium oxyfluoride hydrate, and meanwhile, high-activity titanium metal is provided; chemical nickel plating is adopted, and a nickel catalyst layer is formed on the surface of the high-activity titanium; putting into a tubular furnace, introducing methane gas, and heating for 0.5-5 hours at the temperature of 500-700 DEG C, so as to obtain a finished product. The prepared nano titanium oxide / carbon composite modified layer (NTOC) not only has high corrosion resistance, but also has good conductivity, the structure is compact and uniform, and the binding force with a matrix is high. The adopted preparation method comprises the steps of chemical soaking, replacement plating and methane catalytic pyrolysis. The method is simple in process and equipment, low in cost, easy to operate, short in period, green and environment-friendly, is suitable for large-scale continuous production of the fuel cell bipolar plate, and has a good application prospect.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a nano titanium oxide / carbon composite surface modified titanium-based bipolar plate, a preparation method and application thereof, and belongs to the field of fuel cells. Background Art

[0002] The bipolar plates of proton exchange membrane fuel cells (PEMFC) account for more than 70% of the total mass of the battery and about 30% of the total cost. In fuel cells, the bipolar plates support the battery, conduct current, evenly distribute the cathode and anode gases, and discharge product water, so the bipolar plate materials are required to have good mechanical properties, high conductivity, good air tightness, corrosion resistance, easy processing, mass production, and low cost.

[0003] Bipolar plates can be divided into three categories according to the base material: graphite bipolar plates, metal bipolar plates and composite bipolar plates. Titanium-based metals have always been a hot topic in the research of bipolar plates due to their advantages such as low density, high strength, good machinability, high corrosion resistance and good conductivity. However, an oxide layer is easily formed on the surface of titanium bipolar plates in the air, which will increase the contact resistance between the bipolar plate and the gas diffusion layer, resulting in excessive ohmic losses inside the battery stack. In addition, electrochemical corrosion and dissolution will occur on the titanium surface under the operating environment of the fuel cell. The dissolved metal ions will not only affect the performance of the catalyst but also reduce the proton conductivity of the proton exchange membrane. Therefore, the titanium bipolar plate needs to be surface modified. At present, titanium surface modification coatings are mostly prepared by physical vapor deposition (PVD) (such as multi-arc ion plating, high-power pulsed magnetron sputtering, dual cathode glow discharge plasma technology, etc.), high-temperature element diffusion method and plasma-assisted chemical vapor deposition (CVD) (such as Toyota's patented technology (US2014356764). Although PVD technology can enhance the bonding strength between the coating and the substrate, it often produces an edge effect, making the coating uneven, and then producing defects, resulting in reduced coating stability. CVD technology can greatly improve this shortcoming and improve the uniformity of the coating. However, the coating prepared by conventional CVD has the problem of poor bonding strength. If a modified layer with good bonding strength is to be obtained, additional auxiliary equipment, such as plasma assistance, is usually required. There are also problems such as high process cost, complicated operating conditions and strict process environment requirements. In view of the existing problems, the present invention proposes a surface modification method for titanium-based bipolar plates based on methane pyrolysis carbon deposition effect and oxygen vacancy titanium oxide, which is simple in process, low in cost and easy to operate.

[0004] The thermal decomposition of methane is an endothermic reaction that usually requires a high temperature of more than 900°C to proceed. In order to reduce the temperature required for the reaction and improve energy efficiency, a metal nickel catalyst can be used. Nickel-based catalysts exhibit good catalytic performance in the temperature range of 500-700°C, and can achieve efficient thermal decomposition of methane at lower temperatures. However, during the thermal decomposition of methane, carbon particles will be deposited on the surface of the catalyst and cover the active sites, resulting in a carbon deposition effect and causing the catalyst to deactivate. This is not conducive to the catalytic cracking of methane to produce hydrogen, but this feature can be used to prepare a carbon modified layer on the surface of the titanium bipolar plate, and at the same time, the effect of the pre-nickel layer on the reduced corrosion resistance of the titanium bipolar plate can be eliminated. Summary of the invention

[0005] The present invention aims to provide a method for preparing a titanium-based bipolar plate with a nano-titanium oxide / carbon composite surface modification, which has a simple process, good stability and is suitable for large-scale production. The present invention first removes the oxide film formed on the surface of the titanium bipolar plate in the air, exposes highly active titanium and forms a nano-scale precursor TiOF2·H2O, and then forms a catalytic layer through nickel displacement plating, and utilizes the carbon deposition effect of nickel on the catalytic pyrolysis of methane to form nano-amorphous carbon. During this period, the precursor TiOF2·H2O is thermally decomposed into highly corrosion-resistant nano-oxygen vacancy titanium oxide, and finally a nano-titanium oxide / carbon composite layer is prepared on the surface of the titanium bipolar plate. The prepared nano-titanium oxide / carbon composite modified layer improves the conductivity and corrosion resistance of the titanium-based bipolar plate. The preparation process conditions of the titanium-based bipolar plate with a nano-titanium oxide / carbon composite surface modification are simple, the stability is strong, and it can be used for large-scale production of fuel cells.

[0006] In order to solve the above technical problems, the present invention adopts the following technical solutions: A method for preparing a nano titanium oxide / carbon composite surface modified titanium-based bipolar plate comprises the following steps: 1) Place the titanium bipolar plate in alcohol for ultrasonic cleaning, then rinse and dry it with deionized water several times, then use NH4HF2 solution to remove the oxide film formed on the titanium surface in the air, and finally rinse it with deionized water several times and dry it for later use; 2) preparing a chemical nickel plating solution, and adjusting the pH to 3.0-8.0 with aqueous ammonia for standby use; 3) placing the titanium bipolar plate pre-treated in step 1) in the chemical plating solution of step 2) for a certain temperature and a certain time to react, forming a nickel catalytic layer on the titanium surface, and then ultrasonically cleaning with deionized water and drying; 4) placing the titanium bipolar plate obtained in step 3) into a tube furnace and evacuating the tube furnace; 5) Methane gas is introduced into the tubular furnace of step 4) for heating and heat preservation, and then a nano-titanium oxide / carbon composite surface-modified titanium-based bipolar plate is obtained.

[0007] Furthermore, the oil removal in step 1) is performed by ultrasonic cleaning for 3-10 min, and then ultrasonic cleaning is performed with deionized water for multiple times and dried.

[0008] Furthermore, in step 1), the concentration of NH4HF2 is 0.05-5 mol / L, and the soaking time is 0.5-5 min.

[0009] Further, the preparation method of the chemical nickel plating solution in step 2) is: ethylene glycol 400-800 mL / L, nickel chloride 1-4 g, NH4HF22-5 g, boric acid 0-6 g, lactic acid 0-3 mL, glacial acetic acid 0-20 mL, mix evenly by ultrasonication, dilute to 100 mL volumetric flask, and adjust pH to 3.0-8.0 with ammonia water.

[0010] Furthermore, in step 3), the pre-treated titanium sheet is cleaned and then placed in a chemical plating solution for chemical plating at 20-80° C. for 5-50 min.

[0011] Furthermore, the vacuum degree of the vacuum in step 4) is 0.001-1 Pa.

[0012] Furthermore, in step 5), the methane gas flow rate is 5-30 mL / min, the heating rate is 5-10 °C / min, and the temperature is raised to 500-700 °C and maintained for 0.5-5 h.

[0013] The invention provides a nano titanium oxide / carbon composite surface modified titanium-based bipolar plate prepared by the method.

[0014] Another object of the present invention is to provide the use of the nano titanium oxide / carbon composite surface modified titanium-based bipolar plate prepared by the above method in the preparation of fuel cells.

[0015] The present invention first soaks the titanium bipolar plate in a certain concentration of NH4HF2 solution to remove the oxide film formed on the titanium surface in the air, thereby obtaining uniform nano-TiOF2·H2O and highly active metallic titanium; then, in a chemical plating solution containing nickel ions, a nickel catalytic layer is formed on the surface of the titanium bipolar plate by displacement plating using the potential difference between titanium and nickel; finally, in a methane atmosphere, amorphous carbon is formed on the titanium surface by the carbon deposition effect of nickel on methane catalytic pyrolysis, and at the same time, TiOF2·H2O is decomposed in a high-temperature oxygen-deficient environment to form nano-vacancy titanium oxide with high corrosion resistance, that is, a nano-titanium oxide / carbon composite modified layer (NTOC) is obtained on the surface of the titanium bipolar plate.

[0016] Compared with the prior art, the present invention has the following beneficial effects: (1) The present invention utilizes the carbon deposition effect of nickel on the catalytic pyrolysis of methane to form amorphous carbon on the titanium surface. At the same time, the precursor TiOF2·H2O generated in the process of chemical immersion to remove the oxide film decomposes to form oxygen vacancy titanium oxide, that is, a nano titanium oxide / carbon composite surface modification layer with high corrosion resistance, high conductivity, strong bonding force, and dense and uniformity is obtained. Compared with the existing technologies such as PVD and CVD methods, it has the advantages of high quality of the preparation of the modified layer, simple process, low cost, and easy operation. In addition, after the present invention is applied to the flow field processing of the titanium-based bipolar plate, the high-temperature heat treatment in the preparation process of the nano titanium oxide / carbon composite surface modification layer can also eliminate the internal stress of the titanium bipolar plate formed by the flow field processing.

[0017] (2) The carbon source used in the preparation of the nano-titanium oxide / carbon composite surface modification layer of the present invention is methane gas, and no other additional reducing gas or inert gas is required.

[0018] (3) The nano titanium oxide / carbon composite modified layer prepared by the present invention not only has high corrosion resistance but also has good electrical conductivity, a dense and uniform structure, and strong bonding with the substrate. The preparation methods adopted are chemical immersion, displacement plating, and methane catalytic pyrolysis.

[0019] (4) The process method of the present invention is simple to operate, has a short preparation time, is low cost, is green and environmentally friendly, has high reproducibility, is suitable for large-scale production, and has good application prospects. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0021] Figure 1 This is a grazing incidence X-ray diffraction (GIXRD) spectrum of the titanium-based bipolar plate modified by the nano-titanium oxide / carbon composite surface in Example 1 of the present invention; Figure 2 This is the XPS spectrum of the titanium-based bipolar plate modified by nano-titanium oxide / carbon composite surface in Example 1 of the present invention; Figure 3 This is a Raman graph of the titanium-based bipolar plate modified by the nano-titanium oxide / carbon composite surface in Example 1 of the present invention; Figure 4 This is a surface SEM image of a titanium-based bipolar plate modified with a nano-titanium oxide / carbon composite surface according to Example 1 of the present invention; Figure 5This is a cross-sectional SEM image of a titanium-based bipolar plate with a nano-titanium oxide / carbon composite surface modified in Example 1 of the present invention; Figure 6 The cross-sectional TEM image, high-resolution image and energy spectrum image of the titanium-based bipolar plate modified by the nano-titanium oxide / carbon composite surface in Example 1 of the present invention; TEM image of the NTOC composite layer (b) high-resolution image of amorphous carbon and titanium oxide on the surface of the NTOC composite layer; (cf) energy spectrum image of Ti, O, Ni and C in the NTOC composite layer; Figure 7 This is a graph showing the change in interface contact resistance (ICR) of the titanium-based bipolar plate with nano-titanium oxide / carbon composite surface modification as a function of assembly pressure according to Example 1 of the present invention; Figure 8 The polarization curve of the nano-titanium oxide / carbon composite surface-modified titanium-based bipolar plate of Example 1 of the present invention in a simulated proton exchange membrane fuel cell environment (0.05 mol / L H2SO4+2 ppm HF, 70°C, oxygen flow); Fig. 9 The time-current line of the nano-titanium oxide / carbon composite surface modified titanium-based bipolar plate of Example 1 of the present invention under a simulated proton exchange membrane fuel cell cathode environment (0.05 mol / L H2SO4+2 ppm HF, 70°C, oxygen flow) at a constant potential of 0.6 V for 5 h. DETAILED DESCRIPTION

[0022] The present invention will be further described below in conjunction with specific embodiments. It should be understood that the following embodiments are only used to illustrate the present invention and are not used to limit the scope of the present invention, and those skilled in the art in this field can make some non-essential improvements and adjustments based on the content of the above invention.

[0023] Example 1 A method for preparing a nano titanium oxide / carbon composite surface modified titanium-based bipolar plate comprises the following steps: (1) Pretreatment of titanium bipolar plates: The titanium bipolar plates were ultrasonically cleaned in alcohol for 10 min, then rinsed with deionized water several times and dried. 0.3563 g NH4HF2 was weighed and diluted to a 100 mL volumetric flask with deionized water to obtain a 0.0625 mol / L NH4HF2 solution. The dried titanium bipolar plates were immersed in the NH4HF2 solution for 3 min to remove the surface oxide film and increase the active sites. Finally, the plates were rinsed with deionized water several times and dried for later use.

[0024] (2) Prepare chemical nickel plating solution: 70 mL of ethylene glycol, 2 g of nickel chloride, 23.5 g of NH4HF, 5 g of boric acid, 2 mL of lactic acid, and 18 mL of glacial acetic acid. Mix well by ultrasonication and adjust the volume to a 100 mL volumetric flask. Adjust the pH to about 5.5 with aqueous ammonia.

[0025] (3) The titanium bipolar plate pre-treated in step (1) is placed in the chemical plating solution of step (2) for 30 min at 50° C., ultrasonically cleaned with deionized water, and air-dried.

[0026] (4) Place the titanium bipolar plate obtained in step (3) into a tube furnace, evacuate the tube furnace to 0.01 Pa, and then introduce methane at a rate of 20 mL / min. Set the tube furnace to heat up to 600°C at 5°C / min and keep the temperature for 1 h. A nano-titanium oxide / carbon composite surface-modified titanium-based bipolar plate is obtained.

[0027] 1. Phase analysis The prepared nano-titanium oxide / carbon composite surface modified titanium-based bipolar plate was subjected to grazing incidence X-ray diffraction (GIXRD) analysis with a 2θ angle of 5-90°, a grazing incidence angle of 0.5°, and a scanning speed of 5° / min. The results are as follows: Figure 1 As shown. Figure 1 It can be seen that the prepared nano-titanium oxide / carbon composite surface modified titanium-based bipolar plate has obvious Ti diffraction peaks and rutile TiO2 diffraction peaks.

[0028] The prepared nano-titanium oxide / carbon composite surface modified titanium-based bipolar plate was subjected to X-ray photoelectron spectroscopy (XPS) analysis, and the fine spectrum of O 1s was as follows: Figure 2 As shown, after the O 1s peaks were separated and fitted, it can be seen that the corresponding product at a binding energy of 531 eV is oxygen vacancy titanium oxide, and the corresponding product at a binding energy of 529.6 eV is TiO2, which confirms the test results of GIXRD.

[0029] Figure 3 The Raman graph of the titanium-based bipolar plate modified with nano-titanium oxide / carbon composite surface is at 1348 cm -1 and 1595cm -1 The two peaks near are the D peak (amorphous carbon) and the G peak (ordered graphitized carbon). The peak intensity ratio (I D / I G ) is 1.68, which is greater than 1, indicating that the surface carbon is highly disordered.

[0030] 2. Morphology test The prepared nano-titanium oxide / carbon composite surface modified titanium-based bipolar plate was subjected to scanning electron microscope (SEM) test, such as Figure 4 , as shown in 5.

[0031] Figure 4 This is the surface SEM image of the titanium-based bipolar plate modified with a nano-titanium oxide / carbon composite surface. It can be seen that NTOC is densely and evenly distributed on the surface of the titanium plate.

[0032] Figure 5 This is a cross-sectional SEM image of a titanium-based bipolar plate modified with a nano-titanium oxide / carbon composite surface. It can be seen that the thickness of NTOC is approximately 200 nm.

[0033] Figure 6 The cross-sectional TEM image, high-resolution image and energy spectrum image of the nano-titanium oxide / carbon composite surface modified titanium-based bipolar plate of the present invention are shown in FIG. Figure 6 It can be seen that the surface layer of the modified layer is amorphous carbon of about 10 nm, the middle layer is oxygen vacancy titanium oxide and a small amount of nickel, and the transition layer close to the titanium matrix grows densely and has a high carbon content.

[0034] 3. Interface contact resistance test The contact resistance of the titanium-based bipolar plate modified by nano-titanium oxide / carbon composite surface and the substrate is compared, such as Figure 7 As shown. After the surface modification of nano titanium oxide / carbon composite, the titanium-based bipolar plate has a lower interface contact resistance at 140 N / cm 2 The contact resistance value is 0.56 mΩ cm under the assembly pressure 2 , which greatly improves the substrate (the interface contact resistance value at this pressure is 30.5 mΩ cm 2 )’s surface conductivity meets the use requirements of bipolar plates.

[0035] 4. Corrosion resistance test The corrosion resistance of the nano-titanium oxide / carbon composite surface modified titanium-based bipolar plate was tested using a three-electrode system, in which the nano-titanium oxide / carbon composite surface modified titanium-based bipolar plate was the working electrode, the platinum electrode was the counter electrode, and the saturated calomel electrode was the reference electrode. The proton exchange membrane fuel cell environment was simulated with a 0.05 mol / L H2SO4+2 ppm HF solution at 70°C.

[0036] Figure 8 It is the Tafel curve. It can be seen that the corrosion potential of the titanium-based bipolar plate modified by the nano-titanium oxide / carbon composite surface moves toward the positive direction. The corrosion potential of the modified titanium bipolar plate is 0.39 V, which is higher than 0.17 V of the original titanium bipolar plate, and the passivation current density is significantly lower than that of the original titanium substrate, indicating that NTOC improves the corrosion resistance of the titanium bipolar plate.

[0037] Fig. 9 The time-current curve of the surface-modified titanium-based bipolar plate was tested for 5 h at a constant potential of 0.6 V in a simulated proton exchange membrane fuel cell environment (0.05 mol / L H2SO4+2 ppm HF, 70°C, oxygen). After 5 h of testing, the corrosion current density was maintained at 0.8 μA / cm 2, improving the titanium substrate (corrosion current density of 1.38 μA / cm 2 )’s corrosion resistance and stability meet the use requirements of bipolar plates.

[0038] Example 2 A method for preparing a nano titanium oxide / carbon composite surface modified titanium-based bipolar plate comprises the following steps: (1) Pretreatment of titanium bipolar plates: The titanium bipolar plates were ultrasonically cleaned in alcohol for 10 min, then rinsed with deionized water several times and dried. 14.251 g of NH4HF2 was weighed and diluted to a 50 mL volumetric flask with deionized water to obtain a 5 mol / L NH4HF2 solution. The dried titanium bipolar plates were immersed in the NH4HF2 solution for 0.5 min to remove the surface oxide film and increase the active sites. Finally, the plates were rinsed with deionized water several times and dried for later use.

[0039] (2) Prepare chemical nickel plating solution: 70 mL of ethylene glycol, 2 g of nickel chloride, 23.5 g of NH4HF, 5 g of boric acid, 2 mL of lactic acid, and 18 mL of glacial acetic acid. Mix well by ultrasonication and adjust the volume to a 100 mL volumetric flask. Adjust the pH to about 3.0 with aqueous ammonia.

[0040] (3) The titanium bipolar plate pre-treated in step (1) is placed in the chemical plating solution of step (2) for reaction at 20° C. for 50 min, ultrasonically cleaned with deionized water, and air-dried.

[0041] (4) Place the titanium bipolar plate obtained in step (3) into a tube furnace, evacuate the tube furnace to 0.01 Pa, and then introduce methane at a rate of 5 mL / min. Set the tube furnace to heat up to 500°C at a rate of 10°C / min and keep the temperature for 5 h. A nano-titanium oxide / carbon composite surface-modified titanium-based bipolar plate is obtained.

[0042] Example 3 A method for preparing a nano titanium oxide / carbon composite surface modified titanium-based bipolar plate comprises the following steps: (1) Pretreatment of titanium bipolar plates: The titanium bipolar plates were ultrasonically cleaned in alcohol for 10 min, then rinsed with deionized water several times and dried. 0.3563 g NH4HF2 was weighed and diluted to a 100 mL volumetric flask with deionized water to obtain a 0.0625 mol / L NH4HF2 solution. The dried titanium bipolar plates were immersed in the NH4HF2 solution for 5 min to remove the surface oxide film and increase the active sites. Finally, the plates were rinsed with deionized water several times and dried for later use.

[0043] (2) Prepare chemical nickel plating solution: 70 mL of ethylene glycol, 2 g of nickel chloride, 23.5 g of NH4HF, and 5 g of boric acid. Mix well by ultrasonication and adjust the volume to 100 mL in a volumetric flask. Adjust the pH to about 8.0 with aqueous ammonia.

[0044] (3) The titanium bipolar plate pre-treated in step (1) is placed in the chemical plating solution of step (2) for reaction at 80° C. for 5 min, ultrasonically cleaned with deionized water, and air-dried.

[0045] (4) Place the titanium bipolar plate obtained in step (3) into a tube furnace, evacuate the tube furnace to 0.01 Pa, and then introduce methane at a rate of 30 mL / min. Set the tube furnace to heat up to 700°C at a rate of 10°C / min and keep the temperature for 30 min. A nano-titanium oxide / carbon composite surface-modified titanium-based bipolar plate is obtained.

[0046] Example 4 A method for preparing a nano titanium oxide / carbon composite surface modified titanium-based bipolar plate comprises the following steps: (1) Pretreatment of titanium bipolar plates: The titanium bipolar plates were ultrasonically cleaned in alcohol for 10 min, then rinsed with deionized water several times and dried. 0.3563 g NH4HF2 was weighed and diluted to a 100 mL volumetric flask with deionized water to obtain a 0.0625 mol / L NH4HF2 solution. The dried titanium bipolar plates were immersed in the NH4HF2 solution for 3 min to remove the surface oxide film and increase the active sites. Finally, the plates were rinsed with deionized water several times and dried for later use.

[0047] (2) Prepare chemical nickel plating solution: 80 mL of ethylene glycol, 2 g of nickel chloride, 23.5 g of NH4HF, 5 g of boric acid, 2 mL of lactic acid, and 18 mL of glacial acetic acid. Mix well by ultrasonication and adjust the volume to a 100 mL volumetric flask. Adjust the pH to about 5.5 with aqueous ammonia.

[0048] (3) The titanium bipolar plate pre-treated in step (1) is placed in the chemical plating solution of step (2) for 10 min at 50° C., ultrasonically cleaned with deionized water, and air-dried.

[0049] (4) Place the titanium bipolar plate obtained in step (3) into a tube furnace, evacuate the tube furnace to 0.01 Pa, and then introduce methane at a rate of 20 mL / min. Set the tube furnace to heat up to 600°C at a rate of 5°C / min and keep the temperature for 30 min. A nano-titanium oxide / carbon composite surface-modified titanium-based bipolar plate is obtained.

[0050] Example 5 A method for preparing a nano titanium oxide / carbon composite surface modified titanium-based bipolar plate comprises the following steps: (1) Pretreatment of titanium bipolar plates: The titanium bipolar plates were ultrasonically cleaned in alcohol for 10 min, then rinsed with deionized water several times and dried. 0.3563 g NH4HF2 was weighed and dilute to a 50 mL volumetric flask with deionized water to obtain a 0.125 mol / L NH4HF2 solution. The dried titanium bipolar plates were immersed in the NH4HF2 solution for 10 min to remove the surface oxide film and increase the active sites. Finally, the plates were rinsed with deionized water several times and dried for later use.

[0051] (2) Prepare chemical nickel plating solution: 70 mL of ethylene glycol, 2 g of nickel chloride, 23.5 g of NH4HF, 5 g of boric acid, 2 mL of lactic acid, and 18 mL of glacial acetic acid. Mix well by ultrasonication and adjust the volume to a 100 mL volumetric flask. Adjust the pH to about 4 with aqueous ammonia.

[0052] (3) The titanium bipolar plate pre-treated in step (1) is placed in the chemical plating solution of step (2) for 5 min at 70°C, ultrasonically cleaned with deionized water, and air-dried.

[0053] (4) Place the titanium bipolar plate obtained in step (3) into a tube furnace, evacuate the tube furnace to 0.01 Pa, and then introduce methane at a rate of 5 mL / min. Set the tube furnace to heat up to 600°C at a rate of 5°C / min and keep the temperature for 2 h. A nano-titanium oxide / carbon composite surface-modified titanium-based bipolar plate is obtained.

[0054] Example 6 A method for preparing a nano titanium oxide / carbon composite surface modified titanium-based bipolar plate comprises the following steps: (1) Pretreatment of titanium bipolar plates: The titanium bipolar plates were ultrasonically cleaned in alcohol for 10 min, then rinsed with deionized water several times and dried. 0.3563 g NH4HF2 was weighed and diluted to a 100 mL volumetric flask with deionized water to obtain a 0.0625 mol / L NH4HF2 solution. The dried titanium bipolar plates were immersed in the NH4HF2 solution for 5 min to remove the surface oxide film and increase the active sites. Finally, the plates were rinsed with deionized water several times and dried for later use.

[0055] (2) Prepare chemical nickel plating solution: 70 mL of ethylene glycol, 2 g of nickel chloride, 23.5 g of NH4HF, 5 g of boric acid, 2 mL of lactic acid, and 18 mL of glacial acetic acid. Mix well by ultrasonication and adjust the volume to a 100 mL volumetric flask. Adjust the pH to about 5 with aqueous ammonia.

[0056] (3) The titanium bipolar plate pre-treated in step (1) is placed in the chemical plating solution of step (2) for 30 min at 70° C., ultrasonically cleaned with deionized water, and air-dried.

[0057] (4) Place the titanium bipolar plate obtained in step (3) into a tube furnace, evacuate the tube furnace to 0.01 Pa, and then introduce methane at a rate of 30 mL / min. Set the tube furnace to heat up to 600°C at a rate of 10°C / min and keep the temperature for 1 h. A nano-titanium oxide / carbon composite surface-modified titanium-based bipolar plate is obtained.

[0058] The present invention uses a simple chemical corrosion method to remove the oxide film on the titanium surface and obtain nano-TiOF2·H2O and highly active titanium metal at the same time; using the potential difference between titanium and nickel, a nickel catalytic layer is formed on the surface of the highly active titanium metal by chemical plating; amorphous carbon is formed on the titanium surface by the carbon deposition effect of nickel on the pyrolysis of methane, and at the same time, TiOF2·H2O can form nano-oxygen vacancy titanium oxide with high corrosion resistance under high temperature and oxygen-deficient conditions. The prepared nano-titanium oxide / carbon composite modified layer (NTOC) not only has high corrosion resistance and surface conductivity, but also has strong bonding with the substrate. The method has simple process and equipment, low cost, easy operation, short cycle, and is suitable for large-scale continuous fuel cell bipolar plate production.

[0059] The above shows and describes the basic principles and main features of the present invention and the advantages of the present invention. It should be understood by those skilled in the art that the present invention is not limited to the above embodiments. The above embodiments and descriptions are only for explaining the principles of the present invention. Without departing from the spirit and scope of the present invention, the present invention may have various changes and improvements, which fall within the scope of the present invention to be protected. The scope of protection of the present invention is defined by the attached claims and their equivalents.

Claims

1. A method for preparing a nano titanium oxide / carbon composite surface modified titanium-based bipolar plate, characterized in that: The steps include: 1) Soak the titanium bipolar plate in an alcohol solution to remove oil, dry it, then soak it in a certain concentration of NH4HF2 solution, wash it with deionized water several times, and dry it for later use; 2) Prepare chemical nickel plating solution for standby use; 3) placing the titanium bipolar plate of step 1) in the chemical nickel plating solution of step 2), ultrasonically cleaning it with deionized water for multiple times, and drying it; 4) placing the titanium bipolar plate obtained in step 3) in a tube furnace, and evacuating the tube furnace; 5) Methane gas is introduced into the vacuum tube furnace of step 4) for heating and heat preservation to obtain a nano-titanium oxide / carbon composite surface modified titanium-based bipolar plate.

2. The method for preparing a nano titanium oxide / carbon composite surface modified titanium-based bipolar plate according to claim 1, characterized in that: The titanium bipolar plate material described in step 1) is one or more of pure titanium and titanium alloy.

3. The method for preparing a nano titanium oxide / carbon composite surface modified titanium-based bipolar plate according to claim 1, characterized in that: In step 1), the concentration of the NH4HF2 solution is 0.05-5.0 mol / L, and the soaking time is 0.5-5 min.

4. The method for preparing a nano titanium oxide / carbon composite surface modified titanium-based bipolar plate according to claim 1, characterized in that: In step 2), the chemical nickel plating solution comprises: ethylene glycol 400-800 mL / L, nickel chloride 10-40 g / L, NH4HF220-50 g / L, boric acid 0-60 g / L, lactic acid 0-30 mL / L, glacial acetic acid 0-200 mL / L, pH=3.0-8.

0.

5. The method for preparing a nano titanium oxide / carbon composite surface modified titanium-based bipolar plate according to claim 1, characterized in that: In step 3), the temperature of ultrasonic treatment is 20-80° C., and the time of ultrasonic treatment is 5-50 min.

6. The method for preparing a nano titanium oxide / carbon composite surface modified titanium-based bipolar plate according to claim 1, characterized in that: The vacuum degree of the vacuum pump in step 4) is 0.001-1 Pa.

7. The method for preparing a nano titanium oxide / carbon composite surface modified titanium-based bipolar plate according to claim 1, characterized in that: The flow rate of methane gas in step 5) is 5-30 mL / min.

8. The method for preparing a nano titanium oxide / carbon composite surface modified titanium-based bipolar plate according to claim 1, characterized in that: The heating in step 5) is to increase the temperature to 500-700°C at a rate of 5-10°C / min and keep the temperature for 0.5-5 h.

9. A nano titanium oxide / carbon composite surface modified titanium-based bipolar plate prepared by the preparation method according to any one of claims 1 to 8.

10. Use of the nano titanium oxide / carbon composite surface modified titanium-based bipolar plate as claimed in claim 9 in fuel cells.

Citation Information

Patent Citations

  • Amorphous carbon film, process for forming amorphous carbon film, electrically conductive member and fuel cell bipolar plate having amorphous carbon film

    US20140356764A1